Onion hybrids for more yield - Gupta, Amar Jeet; Mahajan, Vijay; Singh, Major (Indian Horticulture, 2019)
Onion is one of the pioneer crop in which heterosis has been reported for yield and other economic characters. However, in India, at present no commercially viable onion hybrid is available. Eight F1 hybrids, viz. DOGR Hy- 1, DOGR Hy-2, DOGR Hy-3, DOGR Hy-4, DOGR Hy-5, DOGR Hy-7, DOGR Hy-8 and DOGR Hy-50 are promising and being tested at various locations. Among these, DOGR Hy-1 (413.00 q/ha), DOGR Hy-2 (349.60 q/ha) and DOGR Hy-50 (374.55 q/ha) showed 42.84%, 20.91% and 24.11% heterosis, respectively, for bulb yield over the best check in rabi season. DOGR Hy-3 (342.00 q/ha), DOGR Hy-4 (340.80 q/ha) and DOGR Hy-5 (387.25 q/ha) showed 16.22%, 15.81% and 20.11% heterosis, respectively over the best check in kharif season. DOGR Hy-7 (407.50 q/ha) showed 34.88% heterosis over Bhima Red in rabi and also found suitable for kharif. DOGR Hy-8 (544.45 q/ha) showed 23.57% heterosis over Bhima Shakti in late-kharif. Although all hybrids have good storability, are early maturing and free from doubles and bolters, DOGR Hy-7 and DOGR Hy-50 are best in these characters.